Computer-assisted cognitive remediation therapy in schizophrenia: Durability of the effects and cost-utility analysis. (August 2017) - Garrido, Gemma; Penadés, Rafael; Barrios, Maite; Aragay, Núria; Ramos, Irene; Vallès, Vicenç; Faixa, Carlota; Vendrell, Josep M.
Abstract: The durability of computer–assisted cognitive remediation (CACR) therapy over time and the cost-effectiveness of treatment remains unclear. The aim of the current study is to investigate the effectiveness of CACR and to examine the use and cost of acute psychiatric admissions before and after of CACR. Sixty-seven participants were initially recruited. For the follow-up study a total of 33 participants were enrolled, 20 to the CACR condition group and 13 to the active control condition group. All participants were assessed at baseline, post-therapy and 12 months post-therapy on neuropsychology, QoL and self-esteem measurements. The use and cost of acute psychiatric admissions were collected retrospectively at four assessment points: baseline, 12 months post-therapy, 24 months post-therapy, and 36 months post-therapy. The results indicated that treatment effectiveness persisted in the CACR group one year post-therapy on neuropsychological and well-being outcomes. The CACR group showed a clear decrease in the use of acute psychiatric admissions at 12, 24 and 36 months post-therapy, which lowered the global costs the acute psychiatric admissions at 12, 24 and 36 months post-therapy. The CACR is durable over at least a 12-month period, and CACR may be helping to reduce health care costs for schizophrenia patients. Highlights: Treatment effectiveness persisted one year post-therapy on neuropsychological and wellbeing outcomes. The CACR group showed a clear decrease in the use of acute psychiatric admissions. Cognitive Remediation Therapy may be helping to reduce health care costs for schizophrenia.